Effects of Public Spending on Irrigation on Households in the Peruvian Highlands - Hopkins Barriga, Álvaro (2017)
This study assesses the impact that public spending on irrigation has on households in the Peruvian highlands that hold cultivable land and practice agriculture on an independent basis. To this end, we calculated the budget executed for irrigation by central, regional, and local government between 2008 and 2010, which entailed crosschecking the Integrated Financial Administration (System de Administración Financiera, SIAF) database and the National Public Investment Project Bank (Banco de Proyectos del Sistema Nacional de Inversión Pública, SNIP) to adequately identify this expenditure. We applied the differences-in-differences method with control covariates, for which we constructed a pool of households taken from the National Household Survey (Encuesta Nacional de Hogares, Enaho) conducted by the National Institute of Statistics (Instituto Nacional de Estadística, INEI), using the cut-off years of 2007 and 2017 as the baseline and 2012 and 2013 for follow-up. We segmented the sample into two groups based on the incidence of monetary policy by district, per the 2007 Poverty Map: households in poor districts, and households in nonpoor districts. This segmentation allowed us to isolate the endogenous effect of the treatment of using the poverty line calculated for each household in the Enaho. The impacts estimated evince a positive effect on the non-poor households assessed, in the form of an increase in agricultural nonwage income (independent production) and in non-agricultural wage income (non-agricultural dependent activities). In the poor households, the effect on primary and secondary net income and on net agricultural income is statistically equal to zero.